Serum Protein Profile in Women With Pregnancy Morbidity Associated With Antiphospholipid Syndrome (2017)
ABSTRACT: Context: Antiphospholipid antibodies (aPL) are related with a high risk of pregnancy morbidity (PM) and also of vascular thrombosis. On the basis of recent studies, we expect that in women with PM associated with antiphospholipid syndrome (APS), further factors may be deregulated and involved in pathophysiology of the disease. Such factors may have the potential to become novel biomarkers for APS and its stages. Settings and Design: Descriptive study from a recurrent pregnancy loss program. Aims: To study the protein expression in sera from women with PM with or without aPL. Materials and Methods: Protein profiles were determined by surface enhanced laser desorption and ionization − time of flight mass spectrometry (SELDITOF MS) in the serum samples from women with PM, 10 of them with aPL and 12 without aPL. On the basis of the mass-to-charge ratio (m/z) of the protein, signals differentially expressed between the two groups were compared with data banks to approach candidate proteins. Statistical Analysis Used: To determine the differential expression of each protein, a no paired t-test was performed using Ciphergen Express Client 3.1 software. Results: SELDI-TOF analysis makes it possible to discriminate between several proteins in women with PM with and without aPL, although it does not allow protein identification. Nine proteins were found in significantly higher levels in aPL-positive women. Conclusion: The results underline that further factors beyond autoantibodies are involved in PM associated with APS and might lead to the development of new biomarkers.